The Effect of Cold Compresses on Dysmenorrhea in Adolescent Women - Abidah, Siska Nurul; Anggasari, Yasi; Rahayu, Esty Puji; Maulidia, Ella (Jurnal Ilmiah Kesehatan, 2024)
Dysmenorrhea is discomfort during the first day or second day of menstruation that can interfere with the activities of adolescent girls, so that one of them must be treated using non-pharmacological therapy, namely cold compresses. The purpose of this study was to analyze the effect of cold compresses on reducing dysmenorrhea pain in adolescent girls at Pesantren At-Tauhid Sidoresmo Surabaya. The design used in this study is Quasy experimental design with one group pretest posttest desaign using Purposive sampling technique. The sample of this study was conducted at the At-Tauhid Sidoresmo Surabaya Islamic Boarding School as many as 30 adolescent girls who experienced dysmenorrhea. The treatment carried out is cold compress by filling the ice bag as much as 1/3 - ½ part with a temperature of 15 -18 oC as much as 3x every 10 minutes. Data collection of dysmenorrhea pain levels using the Numeric Rating Scale, which assesses pain using a scale of 0-10. Data analysis using Wilcoxon rank test. The results of the analysis of this study indicate that α <0.05, ρ Value = 0.000, which means that there is an effect of cold compresses on reducing dysmenorrhea pain in adolescent girls at the At-Tauhid Sidoresmo Islamic Boarding School in Surabaya. Cold compress therapy has an effect on reducing dysmenorrhea pain, so it can be used as an alternative therapy by young women when experiencing dysmenorrhea pain that does not cause side effects. Keywords: Cold compress, Dysmenorrhea, Adolescents